2017
DOI: 10.1186/s41235-017-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-realistic face masks: a new challenge in person identification

Abstract: We often identify people using face images. This is true in occupational settings such as passport control as well as in everyday social environments. Mapping between images and identities assumes that facial appearance is stable within certain bounds. For example, a person’s apparent age, gender and ethnicity change slowly, if at all. It also assumes that deliberate changes beyond these bounds (i.e., disguises) would be easy to spot. Hyper-realistic face masks overturn these assumptions by allowing the wearer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…The use of the mask was discovered only when the perpetrator decided to remove it mid-flight (Zamost, 2010 ). Despite this report occurring almost a decade ago, and with other such reports also occurring ( see Bernstein, 2010 ), a recent study by Sanders et al ( 2017 ) provided the first assessment of participants’ ability to detect the use of a hyper-realistic silicone mask as a method of physical identity deception. Their research showed that only 6% of participants detected that a confederate was wearing a mask at spontaneous or prompted report, and this rose to just 57% when asked directly.…”
Section: Discussionmentioning
confidence: 89%
“…The use of the mask was discovered only when the perpetrator decided to remove it mid-flight (Zamost, 2010 ). Despite this report occurring almost a decade ago, and with other such reports also occurring ( see Bernstein, 2010 ), a recent study by Sanders et al ( 2017 ) provided the first assessment of participants’ ability to detect the use of a hyper-realistic silicone mask as a method of physical identity deception. Their research showed that only 6% of participants detected that a confederate was wearing a mask at spontaneous or prompted report, and this rose to just 57% when asked directly.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, it almost certainly overestimates the rate of spontaneous detection when a mask framing is absent. Sanders et al ( 2017 ) reported extremely low rates of spontaneous detection, both for photographic presentations in the lab and live viewing of mask wearers outdoors. On the other hand, none of these studies has measured detection during active social interaction with the mask wearer (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of hyper-realistic mask perception have assessed spontaneous detection of masks during an orthogonal task (social inference ratings; Sanders et al, 2017 ). Detection rates approached floor levels in that situation, precluding individual differences analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations